Les eaux de drainage des périmètres irrigués du delta du fleuve Sénégal : systèmes d'évacuation et qualité des eaux - Boubacar Cisse (Physio-Géo)
The option for an irrigated agriculture in the area of the Senegal River delta required from the outsetthe fitting of the drainage systems in the hydro-farming facilities. The achievements show the existence of two draining systems which have different objectives. A superficial drainage essentially aims at leaching the salty soils and at evacuating the surplus of irrigation water. And a subterranean drainage mainly practiced in the sugar bins of Senegalese sugar factory and which role consists in reducing the ground water down to two meters, at a level where it won't jeopardize the plants development. During the growing season, waters are periodically evacuated through a hierarchical drainage network made up with drains of three orders. The irrigated areas are combined with sometimes interlinked drainage outfalls which collect all the farming sewage. The latter is rejected by pumping stations either in natural endoreical depressions (Ndiaël, Krankaye, Noar, Mbeurbeuf and Pardiagne) or in hydraulic axes(Senegal River, Guiers Lake). But despite these drainage systems, the irrigated areas are regularly confronted with some problems of evacuating water. The study reveals the existence of an irrigation water of good quality, which therefore should be continually monitored. On the other hand, the farming drainage waters are very laden withchemical substances from various sources. The identified polluting agentscome from the leaching of salty soils covered by theirrigation water, the pesticide remnants and chemical fertilizers used in farming activities. It is shown in the pesticide tests the presence of some organochlorinated agents in the Natchié drains' drainage water (endosulfan: 1.357 µg; linden:e 0.658 µg) in the Ndiaël drains' (endosulfan: 0.788 µg; lindane: 0.649 µg) and in the Delta outfalls' (endosulfan: 1.349 µg; lindane: 0.747 µg) and someslight heavy metal content.Although theseconcentrationsare low, they can therefore remain for a long time in the environment and by cumulative effects become very harmful on the ecosystem, and on human and animal health.